Establishment of diagnostic reference levels in low-dose renal computed tomography. (February 2023) - Rawashdeh, Mohammad; Saade, Charbel
Background: Increased radiation doses from computed tomography (CT) examinations is well known with proven risks of inducing cancers for effective dose >100 mSv (according to some studies >50 mSvs). Purpose: To establish the diagnostic reference level (DRL) for low-dose renal CT examinations in the evaluation of renal stones. Material and Methods: Patient demographics, CT parameters, and dosimetric indices (CTDIvol and dose length product [DLP]) were collected from 12 tertiary hospitals that routinely perform renal CT in the detection and evaluation of renal stones over a period of 12 weeks. Data obtained from 1418 average-sized patients in each category were recorded. The median values of dosimetric indices for each site were calculated. The DRL values were defined as the 75th percentile of the distribution of the median values of CTDIvol and DLP. Results: There were no significant differences between patient demographics. Mean kVp and mAs for protocols were 121.67 ± 11.56 and 226.91 ± 78.44, respectively. The CTDIvol values were in the range of 2–36.2 mGy, while the DLP values were in the range of 43–1942 mGy.cm. The DRL for the CTDIvol was 16.15 mGy and for the DLP 851.77 mGy.cm. The local median values of CDTIvol and DLP are higher than DRL in two hospitals. Conclusion: Comparison of local median values of CDTIvol and DLP with DRL suggests the needs of an optimization strategy in some hospitals.